Perbedaan Indeks Plak pada Pemeriksaan dengan Bahan Disclosing Solution dan Biji Kesumba (Bixa orellana) - Erwin Erwin; Asmawati Asmawati; Suhikma Sofyan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Dental health practitioners need to consider the use of alternative materials for the examination of plaque indexes derived from natural ingredients as a substitute for disclosing materials because they are not always available despite the high price. one example of this natural ingredient is the kesumba seed plant. The purpose of this study was to determine the differences in plaque index on examination by disclosing solution and kesumba material. This type of research is quasi-experiment. This study used a sample of 47 students from Lawulo Elementary School-aged 9-12 years, data collection was done by checking the PHP plaque index. The results showed that the average plaque index score on examination with a disclosing solution was 3.08, and the average plaque index score on examination with the examination was 2.17 with a difference of 0.91. Statistical test results obtained ρ-value: 0,000 <α (0.05) so that, it can be concluded there are differences in the plaque index on examination with Disclosing solution and examination with kesumba.